FEM Simulation of Acoustic Radiation from Electric Drivelines in Heavy Trucks - Stoyanova, Monika (My University, 2022)
Switching from conventional drivelines to electric drivelines in heavy trucks is a crucial step in the development towards a more sustainable transportation. However, with this change the noise emitted from a vehicle is more tonal compared to the broad-spectrum noise from a vehicle with a combustion engine, which can in some situations be perceived as disturbing. Therefore, it is of interest to study and reduce the noise emission from electric drivelines. In this thesis, the main goal is to develop an efficient method based on finite element method (FEM) to simulate the noise emission from an electric drive unit (EDU) during excitation using the commercial software Abaqus. Using structural-acoustic interaction in Abaqus, the electric drive unit is coupled to the exterior acoustic domain (air) which enables to solve the forward-coupled structural-acoustic problem. To simulate the noise emission in terms of sound pressure, sound intensity, and sound power, direct-solution steady-state dynamic analysis is performed. The obtained acoustic quantities are extracted and further post-processed to be presented in decibel scale (dB). A monopole source was created to verify the employed simulation method by comparing the acoustic pressure to a theoretical value for a spherical geometry of the monopole source. The results from the simulation and the theoretical expression showed a strong correlation which indicates that the modelling of the structural-acoustic interface works properly. This applies also that the electric drive unit couples correctly to the acoustic domain modelled in this thesis. Furthermore, the acoustic boundary conditions were verified by comparing a sphere with non-reflective surface and a hemisphere with no reflection on the surface of the cap and total reflection on the ground of the hemisphere. When comparing a sphere with a hemisphere with the above-mentioned boundary conditions, the expectations are to obtain the same sound power. Running the simulations resulted in the same sound power which means that the boundary conditions are applied correctly. Using the commercial software Abaqus, the forward-coupled structural-acoustic problem can be solved. Both, direct-solution steady-state dynamic analysis and modal-based steady-state dynamic analysis were performed. One of the conclusions that can be drawn is that the direct-solution is more appropriate for solving the exterior acoustic problem than the modal-based solution since it shows a reasonable behavior approaching higher frequencies.